Coral gardening in a changing climate: Rapid assessment of the 4th recorded bleaching event at the Anantara Lagoon and reef system, South Male Atoll, Maldives - Migliaccio, Oriana (Journal of Marine Studies, 2025)
Coral reefs are crucial to marine biodiversity and provide essential ecosystem services, but they face severe threats from climate change, particularly through coral bleaching events. The Maldives, renowned for its diverse coral reefs, has experienced increasing coral bleaching incidents, impacting both marine biodiversity and the tourism-dependent economy. This study investigates the effects of the 2024 coral bleaching event on coral nurseries within the Anantara Lagoon and reef system, South Male Atoll, Maldives. Monitoring was conducted across two coral nurseries in the lagoon and one coral nursery on the natural reef, focusing on species-specific responses to bleaching, predation, and survival rate. Results revealed variability in bleaching impacts among species and locations. Acropora aspera and Acropora muricata exhibited high mortality rates and increased predation, particularly at greater depths (~5 m), while Montipora digitata, Pocillopora damicornis, and Porites cylindrica showed greater resilience. The findings highlight the importance of adaptive management strategies for coral nurseries, emphasizing real-time environmental monitoring and strategic nursery placement to bolster coral reef resilience. This study underscores the need for integrated approaches combining coral restoration with broader reef management practices to enhance ecosystem recovery and sustainability.